Experiential Intelligence : harness the power of experience for personal and business breakthroughs - Kaplan, Soren (Dallas, TX : Matt Holt Books, An Imprint of Benbella Books, Inc., 2023)
"In Experiential Intelligence, award-winning author, former corporate executive, Silicon Valley startup founder, and popular speaker Soren Kaplan reveals how our past experiences impact our present success and future opportunities in ways we often don't recognize"--
Includes bibliographical references (pages 209-211) and index.
Keywords: Experience; Intellect; Success; Success in business